2009
DOI: 10.1007/s10571-008-9337-3
|View full text |Cite
|
Sign up to set email alerts
|

De-differentiation Response of Cultured Astrocytes to Injury Induced by Scratch or Conditioned Culture Medium of Scratch-Insulted Astrocytes

Abstract: Our previous reports indicated that astrocytes (ASTs) in injured adult rat spinal cord underwent a process of de-differentiation, and may acquire the potential of neural stem cells (NSCs). However, the AST de-differentiation and transitional rejuvenation process following injury is still largely unclear. The aim of the present study was to determine whether injured in vitro ASTs can re-enter the multipotential-like stem cell pool and regain NSC characteristics, and to further understand the mechanism of AST de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 53 publications
7
62
0
2
Order By: Relevance
“…Current models of the activation of astrocytes include morphological, migratory, and molecular changes (5). Other key features of this process include growth and proliferative changes, differentiation of quiescent astrocytes, and an increase in the expression of stem cell biomarkers (6). An in vitro scratch assay for the healing of wounds in astrocytes was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Current models of the activation of astrocytes include morphological, migratory, and molecular changes (5). Other key features of this process include growth and proliferative changes, differentiation of quiescent astrocytes, and an increase in the expression of stem cell biomarkers (6). An in vitro scratch assay for the healing of wounds in astrocytes was performed.…”
Section: Resultsmentioning
confidence: 99%
“…In mammals reactive astrocytes form a dense web of interdigitated processes that fill the space vacated by dead or dying cells and which prohibits axonal regeneration (McKeon et al, 1991;Stichel and Müller, 1998). Nevertheless, astrocytes are still one of the main available cellular pools capable of responding to different factors close to injured areas in the mammalian CNS and they can clearly undergo reversion to a proliferative, undifferentiated, stem cell like state (Duggal et al, 1997;Steindler and Laywell, 2003;Chen et al, 2005;Buffo et al, 2008;Yang et al, 2009;Barnabé-Heider et al, 2010). Our results show that like mammalian glial cells, fish glial cells are also the main proliferating cells after SCI that occupy the lesion site and seal the wound.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, unipolar or bipolar GFAPexpressing cells (presumed radial glia) have been identified as the principal source of neurogenesis in the adult mouse (Garcia et al, 2004), revealing the proneurogenic effect of directing astrocyte differentiation into these radial glia. Experiments using astrocyte conditioned medium suggested that astrocytes secrete factors that may influence their ability to regain neuronal progenitor potential and dedifferentiate into radial glia (Yang et al, 2009) and TGF-␣ is one factor has been shown to drive astrocyte bipolar morphology in vitro (Zhou et al, 2001;White et al, 2011). EGF is an additional secreted factor that has been implicated in the dedifferentiation of rat astrocytes in culture (Yu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that, twenty-four hours after the SW, some of the astrocytes close to the wounding site displayed elevated GFAP-immunoreactivity (17). On the contrary, Yang et al (15) reported no change in GFAP content analyzed by immunoblot up to 5 days after the SW. Our results indicate that mRNA levels for GFAP remain unchanged 4 hours after the SW injury to astrocytes. However, ICC analysis of GFAP expression revealed an enhanced immunopositive signal for GFAP in astrocytes surrounding the scratch site.…”
Section: Discussionmentioning
confidence: 97%
“…One of such is a scratchwound assay (SW), first established as a simple, reproducible assay for the analysis of cell migration in vitro (13). The SW model was soon adopted by many to investigate different aspects of astroglial response to mechanical injury (14)(15)(16)(17). As a response to SW injury, the following characteristics of reactive astrocytes have been observed: hyperplasia, enhanced expression of extracellular matrix molecules and elongation of hypertrophic processes (18,19).…”
Section: Kratak Sadr`ajmentioning
confidence: 99%